Contiguous Function Relations for k-Hypergeometric Functions. (10th April 2014) - Mubeen, Shahid; Rahman, Gauhar; Rehman, Abdur; Naz, Mammona
Abstract : In this research work, our aim is to determine the contiguous function relations fork -hypergeometric functions with one parameter corresponding to Gauss fifteen contiguous function relations for hypergeometric functions and also obtain contiguous function relations for two parameters. Throughout in this research paper, we find out the contiguous function relations for both the cases in terms of a new parameterk > 0 . Obviously ifk → 1, then the contiguous function relations fork -hypergeometric functions are Gauss contiguous function relations.